2019
DOI: 10.1021/acs.jmedchem.9b01234
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Characterization of 2-(2,6-Dichlorophenyl)-1-((1S,3R)-5-(3-hydroxy-3-methylbutyl)-3-(hydroxymethyl)-1-methyl-3,4-dihydroisoquinolin-2(1H)-yl)ethan-1-one (LY3154207), a Potent, Subtype Selective, and Orally Available Positive Allosteric Modulator of the Human Dopamine D1 Receptor

Abstract: Clinical development of catechol-based orthosteric agonists of the dopamine D1 receptor has thus far been unsuccessful due to multiple challenges. To address these issues, we identified LY3154207 (3) as a novel, potent, and subtype selective human D1 positive allosteric modulator (PAM) with minimal allosteric agonist activity. Conformational studies showed LY3154207 adopts an unusual boat conformation, and a binding pose with the human D1 receptor was proposed based on this observation. In contrast to orthoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(109 citation statements)
references
References 89 publications
6
100
0
Order By: Relevance
“…Both clinical and pre-clinical studies have demonstrated the importance of DA in MDD and specified the potential therapeutic role of the D1 agonist but limitations such as the biphasic effects of such compounds on higher cognitive functions have prevented the clinical development of any selective D1 agonist for MDD. Lately, a novel potent human D1 positive allosteric modulator, LY3154207, was identified with potential pro-cognitive effects and decreased immobility in the FST in preclinical models (Hao et al, 2019; Svensson et al, 2019). LY3154207 is currently in Phase II clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and pre-clinical studies have demonstrated the importance of DA in MDD and specified the potential therapeutic role of the D1 agonist but limitations such as the biphasic effects of such compounds on higher cognitive functions have prevented the clinical development of any selective D1 agonist for MDD. Lately, a novel potent human D1 positive allosteric modulator, LY3154207, was identified with potential pro-cognitive effects and decreased immobility in the FST in preclinical models (Hao et al, 2019; Svensson et al, 2019). LY3154207 is currently in Phase II clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric modulators represent an alternative and promising strategy for G protein-coupled receptor (GPCR) drug discovery with high selectivity and low side effects. Eli Lilly developed the first clinical D 1 -positive allosteric modulator (PAM), LY3154207 [ 62 , 67 , 68 ], which shows no tachyphylaxis in preclinical animal models [ 62 , 67 , 68 ]. A phase 1 trial of LY3154207 in 80 participants, including healthy participants and PD patients, which studied the safety, tolerability, and PK of multiple ascending doses, was completed in 2017 (NCT02562768).…”
Section: Updates On the Clinical Progress Of Dopaminergic Pd Treatmenmentioning
confidence: 99%
“…This property can be exploited to have safer drugs to use as an adjunctive therapy for schizophrenic patients who have cognitive-resistant deficits. As a matter of fact, the novel D 1 receptor-positive allosteric modulator LY3154207 has now reached the clinic in phase 2 studies for Lewy body dementia [ 77 ]; it would be interesting in future to investigate whether it also improves cognitive symptoms in schizophrenia.…”
Section: Allosteric Modulators As a New Class Of Antipsychoticsmentioning
confidence: 99%